2016
DOI: 10.3389/fsurg.2016.00060
|View full text |Cite|
|
Sign up to set email alerts
|

Cerebral Cavernous Malformations: Review of the Genetic and Protein–Protein Interactions Resulting in Disease Pathogenesis

Abstract: Mutations in the genes KRIT1, CCM2, and PDCD10 are known to result in the formation of cerebral cavernous malformations (CCMs). CCMs are intracranial lesions composed of aberrantly enlarged “cavernous” endothelial channels that can result in cerebral hemorrhage, seizures, and neurologic deficits. Although these genes have been known to be associated with CCMs since the 1990s, numerous discoveries have been made that better elucidate how they and their subsequent protein products are involved in CCM pathogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 48 publications
0
21
0
1
Order By: Relevance
“…Ccm2l (cerebral cavernous malformation 2-like) is a paralog of Ccm2 [56]. CCM2 functions in the CCM signaling [57]. Its paralog (CCM2L) is selectively produced in endothelial cells during angiogenesis [57].…”
Section: ____________________________________________________________mentioning
confidence: 99%
See 1 more Smart Citation
“…Ccm2l (cerebral cavernous malformation 2-like) is a paralog of Ccm2 [56]. CCM2 functions in the CCM signaling [57]. Its paralog (CCM2L) is selectively produced in endothelial cells during angiogenesis [57].…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…CCM2 functions in the CCM signaling [57]. Its paralog (CCM2L) is selectively produced in endothelial cells during angiogenesis [57]. Ccm2l −/− animals exhibited embryonic lethality at E11 associated with myocardial thinning [56].…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…It has been proved by several authors that these three genes play a key role in mechanisms related to vascular development and angiogenesis. A summary of KRIT1, MGC4607 and PDCD10 mutation screening studies in CCM is presented in Table III. The products of these genes are auxiliary membrane proteins that cooperate to secure the interaction between endothelial cells in order to prevent blood leakage [99,100]. Stockton et al demonstrated that KRIT1 and CCM2 are suppressors of the signaling protein RhoA [97,101].…”
Section: Cerebral Cavernous Malformationmentioning
confidence: 99%
“…Recent, occasionally conflicting, findings have contributed to our understanding of the pathogenesis of CCM, and accumulating knowledge of CCM protein interactors might help to elucidate CCM disease pathophysiology. The CCM proteins can be found in a dynamic trimeric complex, with CCM2, a scaffolding protein, acting as the hub and interacting directly with CCM1 and CCM3; however, each also interacts with a variety of other signaling, cytoskeletal, and adaptor proteins [60, 87, 88] (Figure 1C). Several additional direct interactors for each of the CCM proteins have been identified, including, for CCM1, the small GTPase RAP1, the membrane anchor protein heart of glass 1 (HEG1) [89], and the integrin cytoplasmic domain associated protein-1 (ICAP1) [90, 91]; for CCM2, MAPK/ERK kinase kinase-3 (MEKK3) (leading to p38 activation) [92, 93]; and for CCM3, the three Germinal Center Kinase III (GCKIII) serine/threonine (STE20) kinases STK24 and STK25 (via which CCM3 interacts with moesin), and MST4, as well as the scaffolding proteins paxillin and striatin (Figure 1C) [94-100].…”
Section: Hereditary Hemorrhagic Cerebrovascular Diseasementioning
confidence: 99%